2021
DOI: 10.1519/jsc.0000000000004172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Passing Plays on Injury Rates in the National Football League

Abstract: Burke, J, Geller, JS, Perez, JR, Naik, K, Vidal, AF, Baraga, MG, and Kaplan, LD. The effect of passing plays on injury rates in the national football league. J Strength Cond Res 35(12S): S1–S4, 2021—The National Football League (NFL) has one of the highest all-cause injury rates in sports, yet our understanding of extrinsic injury risk factors is limited. The objective of this study was to assess the effect of play type on injury incidence in the NFL. We obtained data for every regular season game played durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(26 reference statements)
0
2
0
1
Order By: Relevance
“…This was supported by the findings by Lee et al 218 where the number of head impacts over 20 g was nearly double for run plays than pass plays in professional players. At the professional level, however, passing plays are associated with a higher odds of SRC than running plays (OR=1.7;95%CI:1.2-1.4), 219 and the risk of SRC has also been related to the primary offensive system used by teams. 220 In either running or passing plays, professional players on the offensive line starting in a down stance (i.e., 3-or 4-point stance) have a higher likelihood of sustaining a head impact than players in an upright (i.e., 2-point) stance.…”
Section: Other Modifiable Risk Factorsmentioning
confidence: 97%
“…This was supported by the findings by Lee et al 218 where the number of head impacts over 20 g was nearly double for run plays than pass plays in professional players. At the professional level, however, passing plays are associated with a higher odds of SRC than running plays (OR=1.7;95%CI:1.2-1.4), 219 and the risk of SRC has also been related to the primary offensive system used by teams. 220 In either running or passing plays, professional players on the offensive line starting in a down stance (i.e., 3-or 4-point stance) have a higher likelihood of sustaining a head impact than players in an upright (i.e., 2-point) stance.…”
Section: Other Modifiable Risk Factorsmentioning
confidence: 97%
“…Media dinding disini mengacu kepada sebuah penciptaan, penyesuaian dan menampilkan suatu alat/sarana dan prasarana yang baru, unik, dan menarik terhadap suatu proses belajar mengajar pendidikan jasmani. Permainan sepakbola sangat di gemari oleh masyarakat seluruh dunia, salah satunya di indonesia mulai dari kota sampai pelosok desa,dari sekolah dasar sampai perguruan tinggi, khusunya sekolah dasar, antusias para siswa sekolah dasar sangat penasaran tentang permainan sepakbola, tetapi masih banyak siswa yang belum paham mengenai tehnik dasar sepakbola khususnya passing (Burke, 2021;Håland, 2020;Hollaus, 2021;Mclean, 2018;Zhou, 2023), hal ini di buktikan banyaknya siswa yang berminat mengikuti pembelajaran sepakbola tetapi terbukti semua anak bisa menendang bola tetapi masih banyak siswa yang belum megerti keterampilan tehnik dasar sepakbola passing (mengoper bola) dengan baik dan benar.…”
Section: Pendahuluanunclassified
“…19,23 It has also been shown that more injuries occur on passing plays overall, though running backs and linemen are more likely to become injured on rushing plays. 11 Although it could be postulated that teams that must play on a shortened week for Thursday Night Football games (as opposed to the typical Sunday NFL games) may have increased injury incidence, 2 studies have shown that the number of days off between games is not associated with increased injury risk, with 1 of the studies demonstrating that the televised Thursday night games have fewer injuries than their weekend counterparts. 19,24 Regarding travel, 1 study found that defensive and offensive linemen who played in the Central time zone were placed on injured reserve more often than those from the Pacific time zone.…”
mentioning
confidence: 99%